Production of the Short film The Line - Agudo, Xavier
As a final work for the Master of Arts in Media Production at the Hochschule Ostwestfalen Lippe in Lemgo, Germany, I took on the task of producing a high quality narrative short film, which could also serve as a festival contender and calling card into the film industry. For this purpose I decided to produce a script with dramatic elements of genres like Drama and Mystery and step into the whole production process of making a Low-No-Budget film. The considerations taken in including elements of Genre, as well as taking a different look on a theme that has been very much exhausted in Germany, like the Berlin Wall, were major points in the developing of the story. Then also adhering to high standard film making in a No- Budget, student production, were major challenges that needed to be overcome. The process and result shows how film making dynamics and new forms of funding and producing can be now carried out with the help of new technologies and Internet presence, achieving high quality results with a very low or nonexistent budget.